Ultra-high energy extragalactic neutrinos interacting with ultra-light dark matter - Barranco, J.; Miranda, O. G.; Moura, C. A.; Rashba, T. I.; Rossi-Torres, F. [UNESP] (IOP Publishing, 2012)
We show the results and discussions of the study of a possible suppression of the extragalactic neutrino flux during its propagation due to a nonstandard interaction with a candidate field to dark matter. In particular, we show the study of neutrino interaction with an ultra-light scalar field. It is shown that the extragalactic neutrino flux may be suppressed by such an interaction, leading to a mechanism to reduce the ultra-high energy neutrino flux. We calculate both the cases of non-self-conjugate as well as self-conjugate ultra-light dark matter. In the first case, the suppression is independent of the neutrino and dark matter masses. We conclude that care must be taken when explaining limits on the neutrino flux through source acceleration mechanisms only, since there could be other mechanisms, as absorption during propagation, for the reduction of the neutrino flux [1], © Published under licence by IOP Publishing Ltd.
Keywords: Acceleration mechanisms; Dark matter; Extragalactic neutrinos; Neutrino fluxes; Neutrino interactions; Scalar fields; Ultra-high energies; Ultra-high energy neutrinos; Ultra-light; Galaxies; High energy physics; Neutrons